2022
DOI: 10.1080/21655979.2022.2078940
|View full text |Cite
|
Sign up to set email alerts
|

CDC25C is a prognostic biomarker and correlated with mitochondrial homeostasis in pancreatic adenocarcinoma

Abstract: Pancreatic adenocarcinoma (PAAD) is a common digestive tract malignant tumor with an extremely poor prognosis. The survival and prognosis may significantly improve if it is diagnosed early. Therefore, identifying biomarkers for early diagnosis is still considered a great clinical challenge in PAAD. Cell Division Cycle 25C (CDC25C), a cardinal cell cycle regulatory protein, directly mediates the G2/M phase and is intimately implicated in tumor development. In the current study, we aim to explore the possible fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Song et al found that the pyrolysis-related gene CASP4 can lead to the progression of pancreatic cancer by promoting fatty acid synthesis and accumulation (32). Other markers, such as AQP5, CDC25C, and TMEM170B, have been proved to be associated with the prognosis of pancreatic cancer (33)(34)(35). A specific single gene, or a group of genes, can predict the prognosis of the tumor in a corresponding way.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al found that the pyrolysis-related gene CASP4 can lead to the progression of pancreatic cancer by promoting fatty acid synthesis and accumulation (32). Other markers, such as AQP5, CDC25C, and TMEM170B, have been proved to be associated with the prognosis of pancreatic cancer (33)(34)(35). A specific single gene, or a group of genes, can predict the prognosis of the tumor in a corresponding way.…”
Section: Discussionmentioning
confidence: 99%